2011
DOI: 10.1007/s11104-011-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar amendment on the soil-atmosphere exchange of greenhouse gases from an intensive subtropical pasture in northern New South Wales, Australia

Abstract: We assessed the effect of biochar incorporation into the soil on the soil-atmosphere exchange of the greenhouse gases (GHG) from an intensive subtropical pasture. For this, we measured N 2 O, CH 4 and CO 2 emissions with high temporal resolution from April to June 2009 in an existing factorial experiment where cattle feedlot biochar had been applied at 10 t ha −1 in November 2006. Over the whole measurement period, significant emissions of N 2 O and CO 2 were observed, whereas a net uptake of CH 4 was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(116 citation statements)
references
References 62 publications
5
106
2
Order By: Relevance
“…To date, several studies have shown that the addition of biochar to soils can mitigate N 2 O emissions in situ from soybean and grass ecosystems [48], following ruminant urine deposition [49], in wheat plots [50] and during laboratory or greenhouse incubations under various conditions [8,9,47,[51][52][53][54][55][56][57][58][59][60][61] while other studies have found no differences or even increases in cumulative N 2 O emissions after biochar addition [61][62][63].…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
“…To date, several studies have shown that the addition of biochar to soils can mitigate N 2 O emissions in situ from soybean and grass ecosystems [48], following ruminant urine deposition [49], in wheat plots [50] and during laboratory or greenhouse incubations under various conditions [8,9,47,[51][52][53][54][55][56][57][58][59][60][61] while other studies have found no differences or even increases in cumulative N 2 O emissions after biochar addition [61][62][63].…”
Section: Mitigation Of Nitrous Oxide Emissions Using Biocharmentioning
confidence: 99%
“…Numerous studies have reported a potential suppressive effect of biochar on N 2 O emissions Spokas et al, 2009;Atkinson et al, 2010;Cayuela et al, 2010;Sohi et al, 2010;Zhang et al, 2010b), as well as some evidence of a neutral effect (Karhu et al, 2011;Scheer et al, 2011). Reductions in soil bulk density, increased soil aeration and possible immobilization of N are among the causes for reduced N 2 O fluxes due to biochar application.…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 99%
“…We used a 12-chamber automated gas-measuring system (Scheer et al 2011) on four treatments within the larger rotation trial. Data from only two of the four treatments are presented in this paper.…”
Section: Experiments 1 and 3: Automated Chambers In Wheat (2010) And mentioning
confidence: 99%